2018
DOI: 10.1051/e3sconf/20187410004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental awareness and behavior of college students in regards to the environment in urban area

Abstract: College students as a community whose behavior and willingness to adopt environmentally sound policies will become a dominant force for sustainable environment in urban area. This research aimed to analyze the environmental awareness of college students, report their environmental behavior, and analyze the correlation of some factors towards environmental awareness and behavior in a sample of 150 college students in one university in Jakarta. Previous studies have shown that demographic characteristics influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…7) High manifestation of healthy lifestyles in the area Community and Environmental Health with 3.68 as its overall mean score. This finding is like that of Ningrum, and Herdiansyah (2018) which revealed that good environmental awareness and behavior are found in college students.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…7) High manifestation of healthy lifestyles in the area Community and Environmental Health with 3.68 as its overall mean score. This finding is like that of Ningrum, and Herdiansyah (2018) which revealed that good environmental awareness and behavior are found in college students.…”
Section: Resultssupporting
confidence: 84%
“…As Ningrum, and Herdiansyah (2018) discussed in their study, there is a need for encouragement by the surrounding condition of the college student/s so that their existing environmental behavior can emerge.…”
Section: Resultsmentioning
confidence: 99%
“…The years of schooling also has positive and significant impact into respondent's waste score. Higher years of schooling lead to higher waste score, meaning that the more educated community will certainly have high awareness on environmental caring [12]. Janmaimool [13] stated the sense of obligation is one of the reasons that push well-educated community to engage in the environmental activities.…”
Section: Resultsmentioning
confidence: 99%
“…However, a difference was found in environmental practices when it comes to gender. 15 In a study conducted among college students in Turkey, their environmental awareness was discovered to be lower than expected. It also found that environmental knowledge does not always influence awareness and behavioral intentions.…”
Section: Introductionmentioning
confidence: 96%